Does terror threaten human rights?: evidence from panel data - Axel Dreher; Martin Gassebner; Lars-H. R. Siemers (Center for Economic Studies and ifo Institute (CESifo), 2007)
The paper presents a political economy model linking terror and governments' respect for human rights. Using panel data for 111 countries over the period 1973-2002, we then empirically analyze whether and to what extent terror affects human rights - measured by three indices covering a wide variety of human rights aspects. According to our results, terror substantially diminishes governments' respect for basic human rights such as absence of extrajudicial killings, political imprisonment, and torture. To some extent, civil rights are also restricted as a consequence of terrorism, while we find no effect of terrorism on empowerment rights.
Keywords: D74; F52; P48; 330; terrorism; human rights; civil liberties; suicide attacks; Politische Gewalt; Menschenrechte; Public Choice; Schätzung; Welt